Silver Recycling From Photo-Processing Waste Using Electrodeposition Method = Pengambilan Perak dari Limbah Pencuci Film Melalui Pengendapan Elektrolitik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Silver electrodeposition of photo-processing waste and without addition of KCN 1,0 M has been studied for silver recycling. Photo procesing waste containing silver in form of (Ag(S203)2 was electrolysed at constant potential and faradic efficiency was determined at various of electrolysis times. Electrolysis of 100 mL photo processing waste without addition of KCN 1,0 M was carried out at constant potential 1.20 Volt, while electrolysis 100 mL photo procesing waste with addition of 10 mL KCN 1,0 M electrolysis was done at 1.30 Volt.The results showed that for silver electrodeposition from photo processing waste with addition of KCN 1,0 M was more favorable with faradic efficiency respectively were 93,16